2021
DOI: 10.3390/languages6040174
|View full text |Cite
|
Sign up to set email alerts
|

On the Primary Influences of Age on Articulation and Phonation in Maximum Performance Tasks

Abstract: Maximum performance tasks have been identified as possible domains where incipient signs of neurological disease may be detected in simple speech and voice samples. However, it is likely that these will simultaneously be influenced by the age and sex of the speaker. In this study, a comprehensive set of acoustic quantifications were collected from the literature and applied to productions of sustained [a] productions and Alternating Motion Rate diadochokinetic (DDK) syllable sequences made by 130 (62 women, 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Parnell & Amerman, 1987;Ryan & Burk, 1974). Findings from acoustic analyses support perceptual changes to speech rate (Karlsson & Hartelius, 2021;Harnsberger et al, 2008;Searle et al, 2002). For example, measuring words produced per minute and syllables per second, Duchin and Mysak (1987) found that speech rate during conversational, sentence repetition, and oral reading tasks decreased across the adult lifespan.…”
Section: Motor Speech Changes With Agingmentioning
confidence: 77%
“…Parnell & Amerman, 1987;Ryan & Burk, 1974). Findings from acoustic analyses support perceptual changes to speech rate (Karlsson & Hartelius, 2021;Harnsberger et al, 2008;Searle et al, 2002). For example, measuring words produced per minute and syllables per second, Duchin and Mysak (1987) found that speech rate during conversational, sentence repetition, and oral reading tasks decreased across the adult lifespan.…”
Section: Motor Speech Changes With Agingmentioning
confidence: 77%
“…In contrast, Decoster and Debruyne (1997) found a greater balance of energy at higher frequencies in older females compared to younger ones in measures comparing H1-H2 (the amplitudes of the first and second harmonics) and E1-45 (mean energy up to 1 kHz and between 4-5 kHz). Karlsson and Hartelius (2021) recently observed complex patterns of age-related change in multiple Mel Frequency Cepstral Coefficients and their variability for sustained /a/: Relative energy increased in some narrow frequency bands, decreased in others, and showed U-shaped patterns in still others. Patterns also differed for men and women.…”
Section: Larynxmentioning
confidence: 99%
“…Our acoustic analysis covers formants (F1, F2) and fundamental frequency (f0), which have been widely studied, and voice quality, which has been assessed less frequently (but see the recent work by Fougeron et al 2021;Karlsson and Hartelius 2021). All parameters can reflect physical effects of aging but may also be conditioned by prosody, specifically whether the filler occurs pre-pausally, post-pausally, or within a speech unit.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Acoustic studies have shown, that effects of aging can impact the level of speech motor control including a slower speech tempo (Amerman & Parnell, 1992) and a reduced vowel space (Thies et al, 2022), especially with an increased instability of speech patterns above the age of 60 years (Karlsson & Hartelius, 2021;. Furthermore, a gradual, non-linear decrease in the degree of coarticulation has been reported for French with a plateau from the mid-50s to 70 years and an abrupt drop beyond 70 years .…”
Section: Lateralization In Onset and Coda English Lateral Consonants:...mentioning
confidence: 99%